Using Energy and Materials More Efficiently: Large and Profitable Potentials, But Little Attention from Energy and Climate Policy - Eberhard Jochem (Vierteljahrshefte zur Wirtschaftsforschung, 2007)
The paper first outlines the challenges the global energy system is facing. It then summarises the present knowledge of energy efficient solutions in all energy using sectors from primary energy to useful energy and, more importantly, from useful energy to energy services (material efficiency and substitution) The examination of these efficiency potentials considers the lifetimes of manufactured artefacts: buildings and infrastructure that will save or waste energy over the next 60 to 70 years. The result - a reduction of present energy use per capita by a factor of 3, labelled the "2000 Watt/cap society", is briefly discussed as are organizational measures and entrepreneurial innovations which could be immediately taken up. Besides discussing the classical reasons why many profitable energy efficiency potentials are not realized, the article also calls for more creativity and trust in the motivation and opportunities of players and for an analysis of the relevant players of the related innovation system. Finally, the recent activities of the Energy Summit of the German government and the Commission's Action Plan for Energy Efficiency are shortly discussed using the criteria developed in the article. – – Der Beitrag skizziert zunächst die gegenwärtigen Herausforderungen an das globale Energiesystem und stellt das vorhandene Wissen zu energieeffizienten Lösungen in allen Sektoren dar. Dabei geht es nicht nur um die Umwandlung von Primär- in Nutzenergie, sondern - wichtiger noch - von Nutzenergie in Energiedienstleistungen (Materialeffizienz und Substitution). Bei der Analyse der Effizienzpotentiale werden die Lebenszyklen von Gebäuden und Infrastruktur berücksichtigt, die den Energieverbrauch der nächsten 60 bis 70 Jahre bestimmen. Das Ergebnis - eine Verminderung des gegenwärtigen Pro-Kopf-Energieverbrauchs um den Faktor 3, auch 2000-Watt-Gesellschaft genannt, wird kurz diskutiert, ebenso wie organisatorische Maßnahmen und unternehmerische Innovationen, die unmittelbar umsetzbar wären. Neben einer Abhandlung der klassischen Gründe für die fehlende Umsetzung profitabler Energieeffizienzpotentiale plädiert der Beitrag für mehr Kreativität und Vertrauen in die Motivation und Gelegenheiten von Akteuren und für eine Analyse der relevanten Akteure des betroffenen Innovationssystems. Abschließend werden die Aktivitäten zum Energiegipfel sowie der Aktionsplan der EU für Energieeffizienz kurz unter Verwendung der entwickelten Kriterien diskutiert.
Keywords: Q28; Q31; Q41; Q54; Q55; 330; Energy efficiency; efficiency potential; energy innovation; energy services; global energy system; energy efficieny policy; Energieeinsparung; Stoffstrommanagement; Energiepolitik; Klimaschutz; Deutschland; EU-Staaten